2002
DOI: 10.1002/ana.10297
|View full text |Cite
|
Sign up to set email alerts
|

Gliomatosis cerebri: Molecular pathology and clinical course

Abstract: Gliomatosis cerebri is a rare, diffusely growing neuroepithelial tumor characterized by extensive brain infiltration involving more than two cerebral lobes. Among 13 patients with gliomatosis cerebri (median age, 46 years), biopsies showed features of diffuse astrocytoma (n = 4), oligoastrocytoma (n = 1), anaplastic astrocytoma (n = 5), anaplastic oligoastrocytoma (n = 1), or glioblastoma (n = 2). Molecular genetic investigation showed TP53 mutations in three of seven tumors and both PTEN mutation and epiderma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 27 publications
2
62
0
1
Order By: Relevance
“…The highly variable course of disease, with median survival of about 30 months after diagnosis and broad variation from a few months to >40 months [7,8,21], also challenges the view that GC comprises a distinct glioma entity. Moreover, molecular studies on GC have reported genetic alterations that are also common in diffuse and anaplastic astrocytic gliomas or glioblastomas, such as isocitrate dehydrogenese 1 (IDH1) mutation, tumor protein 53 (TP53) mutation and epidermal growth factor receptor (EGFR) amplification [4,5,7,9,11,13,14,18,21]. No GC-specific genetic alteration or molecular signature has been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…The highly variable course of disease, with median survival of about 30 months after diagnosis and broad variation from a few months to >40 months [7,8,21], also challenges the view that GC comprises a distinct glioma entity. Moreover, molecular studies on GC have reported genetic alterations that are also common in diffuse and anaplastic astrocytic gliomas or glioblastomas, such as isocitrate dehydrogenese 1 (IDH1) mutation, tumor protein 53 (TP53) mutation and epidermal growth factor receptor (EGFR) amplification [4,5,7,9,11,13,14,18,21]. No GC-specific genetic alteration or molecular signature has been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…3 Extent of resection is a prognostic factor in these tumors, too. 7,15 Although RT (54)(55)(56)(57)(58)(59)(60) Gy, 1.8-2 Gy-fractions) has been considered standard of care for anaplastic oligodendroglial tumors, their chemosensitivity to nitrosoureas and TMZ has long been recognized, and ongoing controversies do not focus on whether to give RT or alkylating chemotherapy at all, but rather when and in what sequence. Long-term results of the two early large independent randomized clinical trials -EORTC 26951 and Radiation Therapy Oncology Group (RTOG) 9402 -that explored the value of PCV polychemotherapy, either prior to or immediately after RT, indicate that the inclusion of chemotherapy in the first-line treatment confers a survival advantage which becomes evident only after follow-up of more than six years and only in the subgroup of patients with 1p/19q-co-deleted tumours.…”
Section: Anaplastic Oligodendroglioma and Oligoastrocytoma -Who Gradementioning
confidence: 99%
“…55,56 The NOA-05 trial explored the efficacy of primary PC chemotherapy, omitting vincristine because of poor blood brain barrier penetration, and observed treatment failure at 8 months in less than half of the patients, and a median overall survival of 30 months. 54 …”
Section: Gliomatosis Cerebri Imaging Resembles Diffuse (Who Grade Ii)mentioning
confidence: 99%
“…Peretti-Viton et al (2002) characterised gliomatosis in humans as a heterogeneous glial proliferation with various degrees of anaplasia. Prognosis of gliomatosis is variable but for at least 50% of patients it is as poor as for glioblastoma (Herrlinger et al 2002). The poor outcome for these patients and low survival rates was also mentioned by Bruna and Velasco (2010).…”
Section: Discussionmentioning
confidence: 97%